Development of polymer bio composites utilising copra waste as filler - Nur Syafiqah Abd Rahman (School of Materials Engineering, University Malaysia Perlis, 2016)
The morphology and mechanical properties of polypropylene reinforced with copra waste have been evaluated to establish the possibility of using it as a new material for engineering applications. The aim of this research was to develop polypropylene (PP) bio-composite reinforced with copra waste (CW). The copra waste was grind, sieved and granules were selected for reinforcement in the polypropylene matrix. The granules are then mixed with polypropylene base material that is Maleic Anhydride Grafted Polypropylene (MA-g-PP) as compatibilizer proportionally in varying parameter of filler loading percentages (10 wt%, 20%, 30% and 40 wt%). It is then mixed to become composite in Z-blade machine at 180 p0sC using a rotor speed of 10 rpm. The mechanical properties of copra were characterized by tensile strength while the chemical structure and morphology was identified with Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) respectively. In this research, the effect of CW addition on the morphological and mechanical properties of PP bio-composite was investigated and the effect of the addition of MA-g-PP as compatibilizer was also carried out. FTIR result showed that at peak 1745.21 cm-1 and 720.23 cm-1 indicated presence of copra waste while after addition of MA-g-PP, peak at 2340.11 cm-1 was observed. SEM showed dispersion and filler pull out. All mechanical properties were improved when treated filler were used. Tensile modulus showed increasing pattern with addition of filler loading whereas decreasing in elongation at break.